AKTIVITAS MEDIA RELATIONS BADAN PENGUSAHAAN (BP) BATAM DALAM MEMBANGUN CITRA POSITIF PERUSAHAAN - Dwi Ayu Lestari; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Badan Pengusahaan (BP) Batam is a government agency that manages the national strategic area of Batam Island which in 2019 took place between the leaders of Pemerintah Kota Batam and Badan Pengusahaan (BP) Batam which was previously chaired by two different people, has become one led by the mayor. This merger led to different reactions in the media so that public relations were required to carry out media relations activities to create a sense of mutual understanding between government agencies and the public, so as to create a positive image. The purpose of this research is to find out how the strategy and the form of media relations activities carried out by Badan Pengusahaan (BP) Batam as well as the perceived supporting and inhibiting factors in building a positive company image.            This study uses a qualitative method with purposive as the determination of 5 informants and accidental sampling for 2 other informants. There are 7 informants as research subjects, while media relations as objects of research. Meanwhile, the data collection technique was done by interview, observation, and documentation. Furthermore, for data validity techniques in the form of participation extension and triangulation.            The results of this study indicate that media relations is to build good relations with the media by establishing intense communication and providing and distributing media needs. Activity media relations of Badan Pengusahaan (BP) Batam include making press releases, press conferences, and reporting on activities. Furthermore, the supporting factors for media relations are the availability of budget and the program implemented is Uji Kompetensi Wartawan (UKW) program. Not only that, public relations maximizes the ability of the team by participating in various training related to public relations and the support of the leader is another supporting factor. In addition to supporting factors, there are also inhibiting factors, namely the apathy of the media and society towards Badan Pengusahaan (BP) Batam.